Synthesis of coumarin derivative using polymer supported reagents - Mhiri, Chiheb; Ternane, Riadh; Hamdi, Naceur; Baklouti, Lassaad (European Journal of Chemistry, 2018)
Recently, there has been a surge in use of polymer-supported reagents and catalysts become common tools for organic synthesis in what is known as polymer-assisted synthesis since they can simplify product isolation and purification. In this context, coumarin derivative 3 was prepared in good yield and high purity, starting from 3-methoxy salicylaldehyde, using reagents supported on a macroporous ion exchange resin. For this purpose, iminocoumarin and unsaturated nitrile were used as starting materials. The synthesized compounds were characterized by IR, NMR and mass spectrometry.